Lukemisia lapsille 4 - Topelius, Zacharias, 1818-1898 (Salt Lake City, UT : Project Gutenberg, 2016)
"Lukemisia lapsille 4" by Zacharias Topelius is a collection of children's stories written in the late 19th century. This work aims to entertain and educate young readers through various tales that often include moral lessons and themes of bravery, kindness, and the importance of faith. The stories encompass a range of topics, likely featuring characters from different walks of life, reflecting values that resonate with children and adults alike. The opening of the book introduces several distinct narratives, starting with a poem that expresses the beauty of nature and the innocence of childhood, followed by the biblical adventure of David and Goliath. In this familiar story, we see King Saul's despair over Goliath's challenge to the Israelites and how the young shepherd David, full of courage and faith, steps forward to confront the giant. The text vividly portrays their interactions, hinting at themes of courage, divine intervention, and the victory of the underdog. The beginning sets the stage for a collection rich in storytelling that combines folklore, culture, and moral education, making it an engaging read for children. (This is an automatically generated summary.)
Wikipedia page about this book: https://fi.wikipedia.org/wiki/Lukemisia_lapsille
Release date is 2016-05-02
Produced by Tapio Riikonen
Keywords: Fairy tales